Reconfigurable method of smart antenna beam shaping in indoor fading environment using adaptive algorithms: An exhaustive experimental study. Issue 1 (7th November 2020) - Imtiaj, SK; Bhattacharya, Sandipan; Misra, Iti Saha
Abstract: Adaptive algorithms for beam shaping of a phased array antenna and multiple‐input multiple‐output (MIMO) system gaining importance in today's advanced wireless networks to mitigate interference effects and distortion in the receiving signal due to multipath, small scale, and large scale fading effects. This article deals with the development of reconfigurable field programmable gate array (FPGA)‐based hardware for smart antenna system to explore parameter dependencies, drawbacks, and relative performance comparison of popular adaptive beamforming and interference suppression algorithms. These are least mean square, recursive least squares (RLS), and sample matrix inversion (SMI) used in real‐time under laboratory environment where the existing wireless channel between transmitters and receivers is linear time‐varying in nature due to presence of secondary sources giving rise to small‐scale fading. For this at first, we propose a novel received signal strength indicator‐based procedure to measure the radiation pattern of the antenna under an echoic indoor environment on a reconfigurable and portable FPGA system named wireless open‐access research platform (WARP), controllable by generic programming codes over a user‐friendly MATLAB interface. For better performance, the SMI algorithm was modified to increase block size rather than block shifting in general SMI. Later a comparative study was performed under varying conditions to observe the best utilization of three adaptive algorithms in beam shaping. In all cases, SMI performs the best with less beam shaping error and faster convergence, validating its use in a real‐time fading environment.